2017
DOI: 10.1097/aud.0000000000000435
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in Cochlear Implant Recipients

Abstract: Speech perception is inherently a multisensory process involving integration of auditory and visual cues. Multisensory integration in cochlear implant (CI) recipients is a unique circumstance in that the integration occurs following auditory deprivation and the provision of hearing via the CI. Despite the clear importance of multisensory cues for perception in general, and for speech intelligibility specifically, the topic of multisensory perceptual benefits in CI users has only recently begun to emerge as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 211 publications
0
53
0
Order By: Relevance
“…Trends observed in animals deprived of visual-auditory experience have also been seen in human patients who had similar restrictions due to congenital cataracts or deafness. Following removal of the congenital cataracts, or the introduction of cochlear implants (especially when done early), these individuals developed the ability to integrate visual-auditory cues; albeit the time frame in which they first showed such capabilities is not entirely clear, and they may always have deficits, especially with complex events (e.g., speech) (Stevenson et al, 2017). Whether more rapid and more pronounced enhancements in performance would be induced with a multisensory training paradigm remains to be determined.…”
mentioning
confidence: 99%
“…Trends observed in animals deprived of visual-auditory experience have also been seen in human patients who had similar restrictions due to congenital cataracts or deafness. Following removal of the congenital cataracts, or the introduction of cochlear implants (especially when done early), these individuals developed the ability to integrate visual-auditory cues; albeit the time frame in which they first showed such capabilities is not entirely clear, and they may always have deficits, especially with complex events (e.g., speech) (Stevenson et al, 2017). Whether more rapid and more pronounced enhancements in performance would be induced with a multisensory training paradigm remains to be determined.…”
mentioning
confidence: 99%
“…They fail to craft the ability to properly synthesize its inputs with those from other modalities (see review by Stein et al, 2014). These defects persist even when later experience is available in a normal housing environment (Xu et al, 2017) and resemble, in a general sense, the multisensory processing abnormalities observed in a number of human psychiatric populations (Brett-Green et al, 2010;Williams et al, 2010;Brandwein et al, 2013;Stevenson et al, 2014Stevenson et al, , 2017Beker et al, 2018). There is significant interest in understanding the mechanisms operating in these defective states.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have suggested that the development of multisensory integration capabilities is shaped by multisensory experience, typically during early life, and that disrupting the acquisition of this experience, or the circuitry needed to properly process that experience, produces defective endpoints (see review by Stein et al, 2014). Anomalous development may help explain the compromised multisensory processing in a number of human populations, contributing to the sensory deficits in Autism Spectrum Disorder, Sensory Processing Disorder, Schizophrenia, and Dyslexia (Brett-Green et al, 2010;Williams et al, 2010;Brandwein et al, 2013;Stevenson et al, 2014Stevenson et al, , 2017Beker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies of AV speech recognition in clinical populations of patients with HL have focused on experienced users of cochlear implants (CIs), devices which restore auditory sensation to the listener (Rabinowitz et al, 1992;Kaiser et al, 2003;Hay McCutcheon et al, 2005;Rouger et al, 2007;Desai et al, 2008;Strelnikov et al, 2009;Altieri et al, 2011;Stevenson et al, 2017;Schreitmüller et al, 2018). For example, several investigators have found that experienced CI users (ECIs) demonstrated stronger reliance on visual cues than NH peers (Desai et al, 2008;Rouger et al, 2008;Leybaert and LaSasso, 2010).…”
mentioning
confidence: 99%